Solomon’s Gold Mine: Description or redescription of 24 species of Caridina (Crustacea: Decapoda: Atyidae) freshwater shrimps from the Solomon Islands, including 11 new species. - de Mazancourt, Valentin; Boseto, David; Marquet, Gerard; Keith, Philippe (European Journal of Taxonomy, 2020)
Following recent (2014–2017) collections made in the Solomon Islands by the MNHN and the NGO ESSI, we provide a checklist of the species of amphidromous freshwater shrimps of the genus Caridina H. Milne Edwards, 1837 from this region. Using morphological as well as molecular data in an integrative taxonomic perspective, we found a total of 24 species, including 11 new for science, that are described or re-described, illustrated and discussed in relation to their habitat and distribution. Newly described species are Caridina barakoma sp. nov., C. choiseul sp. nov., C. intermedia sp. nov., C. maeana sp. nov., C. nana sp. nov., C. piokerai sp. nov., C. pisuku sp. nov., C. paratypus sp. nov., C. poarae sp. nov., C. sikipozo sp. nov. and C. turipi sp. nov. Caridina gueryi Marquet, Keith & Kalfatak, 2009 is re-validated as a species distinct from C. buehleri Roux, 1934. Lectotypes are designated for C. mertoni Roux, 1911 and C. papuana Nobili, 1905. Diagnoses for 6 informative species groups are provided: C. brevicarpalis group, C. gracilirostris group, C. nilotica group, C. typus group, C. serratirostris group and C. weberi group. A map of the species distribution in the Solomon Islands, as well as the phylogenetic relationships between the species and their relatives, are provided.